2018
DOI: 10.1086/699231
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stress Increases the Magnitude of Nonadditive Genetic Variation in Offspring Fitness in the FrogCrinia georgiana

Abstract: When organisms encounter heterogeneous environments, selection may favor the ability of individuals to tailor their phenotypes to suit the prevailing conditions. Understanding the genetic basis of plastic responses is therefore vital for predicting whether susceptible populations can adapt and persist under new selection pressures. Here, we investigated whether there is potential for adaptive plasticity in development time in the quacking frog Crinia georgiana, a species experiencing a drying climate. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 109 publications
5
16
0
Order By: Relevance
“…In a more recent study in this species (also using a North Carolina II breeding design), Rudin‐Bitterli et al. () confirmed high levels of nonadditive genetic variance for offspring fitness, and showed that levels of nonadditive genetic variation were significantly higher when offspring were reared under stressful conditions. In quacking frogs, males force copulation and multiple male amplexus imposes large fitness costs to females through reduced fertilization success (Byrne and Roberts ).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In a more recent study in this species (also using a North Carolina II breeding design), Rudin‐Bitterli et al. () confirmed high levels of nonadditive genetic variance for offspring fitness, and showed that levels of nonadditive genetic variation were significantly higher when offspring were reared under stressful conditions. In quacking frogs, males force copulation and multiple male amplexus imposes large fitness costs to females through reduced fertilization success (Byrne and Roberts ).…”
Section: Discussionmentioning
confidence: 92%
“…; Rudin‐Bitterli et al. ). Causes of environmental‐maternal effects are diverse, but they are typically related to variation in the degree to which females invest in offspring (Wolf and Wade ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations